Normativity of Scientific Law in the Perspective of Neo-Kantian Schools of Thought - FX. Adji Samekto; Ani Purwanti (Hasanuddin Law Review, 2017)
Scientific normativity of law conceived as a character inherent in legal science as a sui generis. Jurisprudence basically studies the law, something that initially emerged from the dogmatic belief in philosophy. Dogmatism refuse to alter beliefs one iota. The teachings of dogmatic philosophy stem from the teachings of Plato and reflected in the legal enforceability. Dogmatism in the law is reflected in the Corpus Juris Civilis. Along with the development of post Era Scholastic philosophical thinking, the philosophy synthesizes thought between dogmatic thinking and skeptic has appeared in the Age of Enlightenment. This idea is reflected in Transcendental Idealist philosophy thought of Immanuel Kant. The core idea is that real human beings are given the ability to understand based on empirical experience and actually also able to gain an understanding of the human being that is the essence of symptoms. Transcendental Idealist, thus dynamic, moving to look for values that are useful for life. Transcendental Idealist thought then be adopted Kelsen in the teaching of normativity in legal positivism. Normativity in the teachings of Hans Kelsen’s legal positivism derived from the integration of empirical positivism and idealistic empiricism.